Enzyme production by soil filamentous fungi under solid-state fermentation in banana stalk - Castro Pires dos Santos, Fernanda; Barbosa Cunha, Joice Raísa; do val de Assis, Fábia Giovana; Lopes Leal, Patrícia (Federal University of Piauí, 2018)
The adequate disposal of agricultural waste is one of the major concerns of public officials and a research challenge to obtain sustainable solutions to the problem. In this sense, the objective of this study was to evaluate the banana leaf stalk use as substrate in solid-state fermentation (SSF) for production of amylolytic and cellulolytic enzymes by Penicillium spp. LEMI A11 strain grown under different substrate concentrations, pH and temperature. Effects of different pH conditions (5.0 and 6.0), temperature (30 and 35 °C) and substrate concentration 70 and 90% (in relation to the final volume) of the fermentation were evaluated over 120 hours of fermentation. The results indicated that Penicillium spp. LEMI A11 was able to use the banana stalk as substrate under SSF. The maximum activities for amylase dextraining, amylase saccharifying and CMCase were 0.18; 0.13 and 04 U.g-1, respectively. The effect of environmental factors related to the substrate concentration was significant for saccharifying amylase and CMCase activity only. The interaction between the environmental factors tested was significant for the dextrinizing amylase activity only. It was verified enzyme activity reduction after 96 hours of fermentation for all enzymes. It concluded that banana stalk is an alternative carbon source to be used in SSF for enzyme production by of Penicillium spp. LEMI A11.